Functional Cooperation between KCa3.1 and TRPV4 Channels in Bronchial Smooth Muscle Cell Proliferation Associated with Chronic Asthma - Yu, Zhihua; Wang, Yanxia; Qin, Lu; Chen, Hongzhuan (Frontiers in Pharmacology, 2017)
Abstract Airway smooth muscle cells (SMC) proliferation contributes to the airways remodeling and irreversible airway obstruction during severe asthma, but the mechanisms of airway SMC proliferation are poorly understood. Intracellular Ca2+ levels play an important role in regulating cell proliferation. We have previously reported KCa3.1 channels regulated human bronchial smooth muscle (HBSM) cells proliferation via the Ca2+ influx as a consequence of membrane hyperpolarization. However, the role of potassium channels KCa3.1 in airway remodeling as well as the mechanism for extracellular Ca2+ influx induced by the activation of KCa3.1 remains unknown. Here we demonstrated that KCa3.1 channels deficiency attenuated airway remodeling, airway inflammation, and airway hyperresponsiveness (AHR) in a mouse model of chronic asthma. The gene expressions of repressor element 1-silencing transcription factor (REST) and c-Jun, two transcriptional regulators of KCa3.1 channels, were correlated negatively or positively with KCa3.1 channels expressions both in vivo and in vitro using real-time PCR and Western blot analyses. RNAi-mediated knockdown or pharmacological blockade of KCa3.1 and TRPV4 significantly attenuated HBSM cells proliferation. Using confocal imaging and custom data analysis software, blockade of TRPV4 decreased the Ca2+ influx induced by 1-EBIO-mediated KCa3.1 activation. Double-labeled staining showed that KCa3.1 and TRPV4 channels colocalized in HBSM cells. These results demonstrate that KCa3.1 channels regulate the proliferation phenotype of HBSM cells via TRPV4 channels in the process of chronic asthma, making it a potential therapeutic target to treat chronic asthma.